Stability analysis of large-scale functional differential systems - Martynyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
The present paper is focused on a new method for analysis of stability of solutions of a large-scale functional differential system via matrix-valued Lyapunov-Krasovskii functionals. The stability conditions are based on information about the dynamical behavior of subsystems of the general system and properties of the functions of interconnection between them.